PERTUMBUHAN DAN PRODUKSI DUA VARIETAS TANAMAN SELADA PADA BERBAGAI TINGKAT NAUNGAN DAN KOMPOSISI MEDIA TANAM. - Mawar, Mawar; Safriadi, Safriadi (Universitas Muhammadiyah Makassar, 2024)
ABSTRACT The research aimed to determine the effect of shade level, variety and composition of planting media on the growth and production of lettuce plants. The research was carried out in Palae Village, South Sinjai District, Sinjai Regency, South Sulawesi Province from February to April 2024. The research was carried out in a separate plot design using a three-factor factorial pattern. The first factor was shade as the main plot, which consists of three levels, namely no shade, Paranet 85% and Paranet 65%. The second factor was the variety as a subplot, which consists of two levels, namely Grand Rapids and Red Rapids. The third factor was the composition of the planting media as sub-plots, which consists of two levels, namely soil + goat manure, and soil + cow manure.The results of the research showed that there was not one variety, level of shade, composition of planting media that had a better influence on the growth and production of lettuce plants, but the interaction between treatment without shade and the Grand Rapids variety and composition of soil media + cow manure resulted in height of lettuce plants. The highest is 26.35 cm and the highest leaf area was 95.90 cm2